Associations of Musical Activities and Positive Affect With Fear of Childbirth: A Structural Equation Modeling Approach - Liu, Shidi; Jin, Yi; Li, Hongmei; Zeng, Tingting; Zhou, Ge; Yu, Lili; Fan, Yao; Lei, Xun (Frontiers in Public Health, 2022)
Background: Fear of childbirth is a prevalent issue among women, with a wide range of interventions to dispel it. Here we explored a novel and beneficial intervention and one possible influence mechanism of it. Methods: The cross-sectional study recruited 1053 pregnant women from one tertiary-grade A class hospital between March to August 2021. The questionnaire included demographic characteristics, a self-made musical activities questionnaire, the Positive affect subscale, and the Childbirth Attitudes Questionnaire. We parceled the eight musical activities into three items by item parceling methodology. The associations of musical activities and positive affect with fear of childbirth were evaluated by a structural equation modeling approach. Results: Our analyses demonstrated the effectiveness of musical activities, which was notably correlated with the increase in positive affect(β=0.309, P<0.01). On the contrary, positive affect predicted a decrease in fear of childbirth(β=-0.085, P=0.019). Additionally, positive affect mediated the effect of musical activities on fear of childbirth(β=-0.026, P=0.030). However, the direct effect of musical activities on fear of childbirth was not found(β=0.029, P=0.514). Conclusions: Relying on musical activities alone may not be adequate to alleviate the fear of childbirth, and positive affect played a pivotal role between musical activities and fear of childbirth. The results showed that musical activities would be an effective non-pharmaceutical way to alleviate the fear of childbirth and positive affect can not be ignorant in future childbirth fear reduction programs.